Phenolic and antioxidant evaluation in Prosopis laevigata wood and Acrocarpus fraxinifolius bark - Ibarra-Berumen, Jorge; Ordaz-Pichardo, Cynthia; Rosales-Castro, Martha (Instituto de Ecología, A.C., 2023)
During forest harvesting of Prosopis laevigata (mesquite) and Acrocarpus fraxinifolius (pink cedar) species, waste products are generated, both of wood and bark. This material contains secondary metabolites such as phenolic compounds that have potential in pharmaceutical areas. The objective of this work was to obtain extracts of P. laevigata wood and A. fraxinifolius bark, using different extraction solvents and different temperatures, in order increase yield, phenols, flavonoids and proanthocyanidins, as well as to show the importance of yield when the results are expressed on plant material basis. The in vitro antioxidant capacity of the extracts was evaluated, and their phenolic compounds were identified by UPLC/MS.  In P. laevigata wood, the best extraction conditions were with ethyl acetate at 60°C for results based on dry extract, and ethanol 70% at 60 °C, for results based on wood. Its main compounds were catechin, taxifolin, eriodictyol, and protocatechuic acid. In A. fraxinifolius bark, 70% ethanol and temperatures of 50 °C and 60 °C favored the increase of phenolic compounds and the antioxidant capacity. The main compounds identified were gallic acid, taxifolin, luteolin, apigenin and catechin. The results provide information on the use of P. laevigata wood, so far unexplored as a source of phenolic compounds with potential applications in pharmacological areas, and on extraction conditions to improve the concentration of phenolic compounds in A. fraxinifolius bark.